Cyber security basics protect your organization by applying the fundamentals - Franke, Don ([Don Franke], 2016)
This book covers concepts and controls. It is a good primer for those new to the field and a refresher for the more seasoned practitioner. It is for those who are tasked with creating, leading, supporting or improving an organization's cyber security program. The goal is to help clear some of the fog that can get in the way of implementing cyber security best practices." -- Back cover